RANCANGAN SISTEM INFORMASI AKUNTANSI PERSEDIAAN KOPERASI PAGUYUBAN KARYAWAN DEKABE JAWA TIMUR - Titin Nur Hidayah; Hariadi Yutanto; Ellen Theresia Sihotang (Bina Ekonomi, 2023)
The rapid development of information technology has brought changes to all aspects of individuals and organizations, one of which is cooperatives. The Cooperative Association of Pakar Dekabe employees (Pakar Dekabe Cooperative), has trading and service business activities. Its trading business activities are related to buying, selling, and managing merchandise inventory that require recording and reporting. Recording sales as inventory expenditure is still done manually. Inventory is updated at the end of the current month period. This has an impact on inventory information that is not up-to-date and there is the potential for physical discrepancies to occur in recording. In this regard, the purpose of this study is to develop an inventory accounting information system through the Excel for Accounting (EFA) application to produce financial information accurately and qualified for stakeholders. The result of this study is the design of the EFA with the development of the number of working sheets from three become 11 sheets in order to detail the recording transactions, avoid the occurrence of physical discrepancies and recording inventory and also simplify the process of preparing financial reports as part of the internal control implementation.